EVALUATION OF ENGLISH SPECIFIC PURPOSES TEXTBOOK USED IN MANAGEMENT BUSINESS MAJOR IN VOCATIONAL HIGH SCHOOL - Tina Endriani; Isry Laila Syathroh (PROJECT (Professional Journal of English Education), 2022)
This study is an attempt to evaluate the suitability of the “Master Your Business Communication Skill” book written by Ismanthono (2017) as an English Specific Purposes (ESP) book for management business major in vocational high school. To meet this aim, the viewpoints of 3 teachers and 22 students of vocational high school are collected through Daoud and Celce-Muria’s (1979) ELT textbook evaluation checklist. The opinions of the ESP teachers toward ESP textbook are positive. Based on the result of the checklist, the teachers and students state that this book is useful in the teaching and learning process, especially vocational high school students majoring in business management. As the conclusion, in terms of subject matter, this book is suitable to be used as a textbook or at least as a complement to existing ESP books. In terms of vocabulary, this book is sufficient and in accordance with the students’ needs of management majors. Then in terms of exercises, a half of the participants agree that the exercises in the book can help increase understanding of the materials. While in terms of illustration, the participants think that the illustration in this book is interesting and easy to understand. Finally, in terms of physical make-up such as cover and title, this book is attractive enough. The cover reflects the content of the book and also provides the prospective readers at the first look. Keywords:  ESP, Textbook Evaluation, Checklist